Distúrbio de voz e síndrome de Burnout em docentes - Brito, Aline Ferreira de (2015)
To analyze the association between the probable Voice Disorder presence and Burnout Syndrome in teachers of public elementary schools of a city in Sergipe. Method: This research, of a Cross-Sectional nature, was initially referred to the Ethics Committee of the Pontifícia Universidade Católica de São Paulo. The selected city has 708 teachers in its elementary schools. The sample, stratified random type, by area and teaching staff, consisted of 208 teachers. The participants were informed of the study procedures and performed reading and signing of the Terms of Free and Informed Consent. All subjects were submitted to the following instruments: Vocal Production Condition Teacher (VPC-T), Screening Index for Voice Disorder (SIVD), and Questionnaire for the Evaluation of Burnout Syndrome because of Labor (QEBSL). Regarding the VPC-T, the data concerning sociodemographic aspects, employment status and work organization was submitted to numerical and percentage analysis to describe the group of participants. To set the subjects with probable Voice Disorder, it was considered the SIVD score with score ≥ 5 of symptoms in "sometimes" and "always" frequency. The QEBSL was analyzed considering their domains, and the presence of Burnout syndrome was recorded when the teacher had low scores on the Illusion by the work dimension (<2) and high scores in Psychic Exhaustion, Indolence/ Depersonalization and Guilt (≥ 2). A grouping of these subscales was performed, and participants were divided into two groups: those who had not or had one of the positive subscales; and those with two to four positive scales. A descriptive analysis of data was performed and, for the association between the voice disorder and the Burnout Syndrome were applied univariate and multiple logistic regression models. Results: The 208 teachers had an average age of 41 years old (median: 40 years), ranging from 22.9 to 66.3 years and average career span of 16.1 years (median: 15.1 years). Of these, 66.9% were female, 67.3% from the rural area and 64.4% had probable Voice Disorder. The teachers with more than 15 years of career presented nearly twice as likely chance of Voice Disorder. Regarding the organization of work, 70.5% considered the work repetitive and 78% said that perform intense physical exertion at work. Of the symptoms listed in SIVD, were highlighted dry throat (88.1%), hoarseness (84.4%) and vocal fatigue (82.1%). Regarding the Burnout scales, it was found that the Psychic Exhaustion had a higher percentage among the others (30.3%). In the association between probable Voice Disorders and the Burnout scales, it was registered that teachers who presented Psychic Exhaustion had a chance of OR = 1.78 (p <0.001) (²= 84,1%) for the probable Voice Disorder. In the grouping, the teachers with positivity for two to four Burnout scales recorded a chance of OR = 4.01 (p = 0.013) (² = 86.2%) to present the probable Voice Disorder. Conclusion: It was confirmed the presence of the association between the probable Voice Disorder and the Burnout Syndrome